In Situ X‑Ray Diffraction Study on Hydrate Formation at Low Temperature in a High Vacuum - Bauer, Robert P.C; Ravichandran, Aravind; Tse, John S; Appathurai, Narayan; King, Graham; Moreno, Beatriz; Desgreniers, Serge; Sammynaiken, Ramaswami (Journal of physical chemistry. C, 2021)
The condition for incorporating simple gases with H2O to form clathrate hydrates in protosolar nebula is a subject of topical interest. Methane and carbon dioxide clathrate hydrates have been speculated to exist in outer solar system bodies, but they have eluded direct detection so far. We have constructed a low-temperature and high-vacuum system to prepare and study clathrate hydrates by in situ synchrotron X-ray diffraction experiments. Upon heating, we found clathrate hydrates can be obtained from the codeposition of methane or carbon dioxide with water outside the equilibrium thermodynamic stability region under high vacuum. We suggested that the hydrate formation is assisted by the phase transformations in the ice, which provide the necessary activation energy to increase the mobility of the guest and water molecules. The results provide a new perspective on how “metastable” gas hydrate can be formed.